QUANTITATIVE MULTI-OBJECTIVE EVALUATION OF CONSUMER DATA MANAGEMENT TOWARDS EFFECTIVE DECISION MAKING IN TOURIST RESORT - Dimitrios J.Dimitriou (International Journal of Research Science and Management, 2017)
The paper deals with the key factors affecting tourist resorts management in effective decision making. The evaluation methodology based on effective use of information received and addressed to resort clients, highlighting the key decision objectives, variables and information resources. Based on functional analysis, the framework for an effective capability driven DSS system is discussed and the data driven functions are presented. The results of an application to medium size summer holiday resorts in Alexandroupolis region in Northern Greece are discussed, providing key messages to planners, decision makers and managers providing the key principles of use of the clients’ information towards effective decision making, resilience business and productive management.